Young Adult Cancer Survivorship: Recommendations for Patient Follow-up, Exercise Therapy, and Research. Issue 1 (28th October 2020) - Adams, Scott C; Herman, Jennifer; Lega, Iliana C; Mitchell, Laura; Hodgson, David; Edelstein, Kim; Travis, Lois B; Sabiston, Catherine M; Thavendiranathan, Paaladinesh; Gupta, Abha A
Abstract: Survivors of adolescent and young adult cancers (AYAs) often live 50 to 60 years beyond their diagnosis. This rapidly growing cohort is at increased risk for cancer- and treatment-related 'late effects' that persist for decades into survivorship. Recognition of similar issues in pediatric cancer survivors has prompted the development of evidence-based guidelines for late effects screening and care. However, corresponding evidence-based guidelines for AYAs have not been developed. We hosted an AYA survivorship symposium for a large group of multidisciplinary AYA stakeholders (approximately 200 were in attendance) at Princess Margaret Cancer Centre (Toronto, Ontario, Canada) to begin addressing this disparity. The following overview briefly summarizes and discusses the symposium's stakeholder-identified high-priority targets for late effects screening and care and highlights knowledge gaps to direct future research in the field of AYA survivorship. This overview, although not exhaustive, is intended to stimulate clinicians to consider these high-priority screening and care targets when seeing survivors in clinical settings and, ultimately, to support the development of evidence-based late effects screening and care guidelines for AYAs.